Labor market policies and IMF advice in advanced economies during the Great Recession - Olivier J. Blanchard; Florence Jaumotte; Prakash Loungani (IZA Journal of Labor Policy, 2014)
In this paper we present and analyze the IMF's labor market recommendations for advanced economies since the beginning of the crisis, both in general and specifically in program countries. Our analysis is informed by our reading of the theoretical and empirical literature on the design of labor market policies and institutions in advanced economies. We organize our discussion around two concepts: micro flexibility, namely the ability of the economy to allow for the reallocation of workers to jobs needed to sustain growth; and macro flexibility, namely the ability of the economy to adjust to macroeconomic shocks. Achieving both types of flexibility while protecting workers and maintaining incentives for workers and firms to invest in existing relations, is not that simple, and the design of labor market institutions faces delicate trade-offs.
Keywords: E2; J3; J5; J6; 330; Unemployment; Labor market institutions; Great Recession